INSTRUCTIONAL MATERIALS OF SOCIAL COMUNICATION AND SCIENCES DEVELOPT BY ESP FOR UNDERGRADUATE STUDENTS OF PUBLIC ADMINISTRATION DEPARTMENTS IN STISOSPOL â€œWASKITA DHARMAâ€ MALANG PERIODE 2014-2015: Instructional Materials, English for Specific Purposes (ESP), Public Administration Departments - Syakur, Abd (STISOSPOL WASKITA DHARMA, 2015)
This study aimed at investigating the syllabus and materials of Public Administration Departments of the College of social and communication at Stisospol â€œWaskita Dharmaâ€ Malang and to provide solutions to these problems. For this purpose, four research questions were posed and the answers to these questions were provided and discussed. The data for the study were collected via (face-to-face) interviews. The informants of this study were undergraduate students from the College of Social at Stisospol â€œWaskita Dharmaâ€ Malang for the academic year 2014-2015. The findings of the study revealed that the students faced problems in relation to vocabulary register, organization of ideas, grammar, spelling, and referencing. ESP for Public Administration Departments is not developed at Stisospol â€œWaskita Dharmaâ€ Malang. This study is aimed to develop ESP instructional materials with the principles of CTL for undergraduate students of Public Administration Departments. There are two major stages applied in this study namely Research, to discover the needs of the students in needs analysis, and Development, to develop the ESP instructional materials. The development stage covers FGD, writing manuscript, expert judgment, revision, expert validation, and tryouts. It can be said that through the entire steps of Research and Development, the products of materials are trustworthy and appropriate to apply at Public Administration Departments in Stisospol â€œWaskita Dharmaâ€ Malang.